A thrombopoietin receptor agonist to rescue an unusual platelet transfusion-induced reaction in a p.V1316M-associated von Willebrand disease type 2B patient. (February 2022) - Casari, Caterina; Favier, Remi; Legendre, Paulette; Kauskot, Alexandre; Adam, Frederic; Picard, Veronique; Lenting, Peter J.; Denis, Cecile V.; Proulle, Valerie
This report describes the first case of splenic injury in a patient with p.V1316M-associated von Willebrand disease type 2B (VWD2B) with chronic thrombocytopenia, successfully treated with nonoperative management including von Willebrand factor (VWF) replacement therapy, and platelet transfusions relayed by a thrombopoietin receptor agonist (TPO-RA, Eltrombopag). Eltrombopag was initially introduced to rescue an unusual post-platelet-transfusion reaction exacerbating the thrombocytopenia. In-depth analysis of the dramatic platelet count drop and VWF measurements timeline ruled out an allo-immune reaction and supported an alternative hypothesis of a sudden platelet clearance as a consequence of stress-induced release of abnormal VWF. One year later, a second life-threatening bleeding episode required urgent surgery successfully managed with VWF replacement therapy and platelet transfusions. Eltrombopag was further introduced in the post-surgery period to allow bleeding-free and platelet-transfusion-free successful recovery. Treatment decisions are particularly challenging in patients with VWD2B, and this case highlights how such decisions can benefit from understanding the molecular origin of platelet count fluctuations observed in these patients. Here, we successfully used a new therapeutic approach combining VWF-replacement therapy and initial platelet-transfusion relayed by TPO-RA to optimize patient management. Plain language summary: A combination of von Willebrand factor replacement and thrombopoietin receptor agonist in thrombocytopenic patients with von Willebrand disease type 2B: a new therapy approach to optimize patient management? Therapeutic management of patients with von Willebrand disease type 2B are particularly challenging in case of severe thrombocytopenia. Treatment includes von Willebrands factor replacement therapy and iterative platelet transfusions. We describe the first case of splenic injury in a patient with p.V1316M-associated von Willebrand disease type 2B successfully treated with nonoperative management including von Willebrand factor replacement therapy and platelet transfusions relayed by a thrombopoietin receptor agonist. We showed that the unusual post-platelet-transfusion reaction associated with a dramatic platelet count drop was a consequence of stress-induced release of abnormal von Willebrand factor. The combination of von Willebrand factor replacement therapy and thrombopoietin receptor agonist may offer a new therapeutic approach to optimize patient management.